The Meaning of The Ikhtilāf Al-madhāhib In 'Abd Al-wahhāb Al-sha'rānī's Al-mīzān Al-kubrā - Pagani, Samuela (Islamic law and society, 2004)
Abstract The Mīzān kubrā by 'Abd al-Wahhāb al-ShaAErānī (d. 973/1565) was cited by nineteenth-century Muslim scholars to support a wide range of mutually exclusive conceptions of religious authority. In the twentieth century, modern students of Islamic law have given different assessments of ShaAErānī's view of the relationship between the madhāhib: while some stress its innovativeness and potential for legal reform, others regard it as a conservative restatement of scholastic tradition. In substantial agreement with the latter view, I discuss some of ShaAErānī's theories, focusing on the significance of his peculiar blending of Sufi and legal discourses for the cultural history of Islam in the early Ottoman period. I argue that ShaAErānī's aim is to bring Ibn 'Arabī's spiritual hermeneutics of the revelation into line with the "age of taqlīd." As a "legal theorist" no less than a h agiographer, ShaAErānī was an imaginative and reliable witness of the religious values and mentalités of his time. Far from calling into question the established system of the legal schools, he assigned a pivotal role to the metaphysical validation of ikhtilāf in order to strengthen a pluralist view of mainstream Islam.